2014
DOI: 10.1002/hbm.22696
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical analysis as a distributed neurobiological function

Abstract: Language processing engages large-scale functional networks in both hemispheres. Although it is widely accepted that left perisylvian regions have a key role in supporting complex grammatical computations, patient data suggest that some aspects of grammatical processing could be supported bilaterally. We investigated the distribution and the nature of grammatical computations across language processing networks by comparing two types of combinatorial grammatical sequences—inflectionally complex words and minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 56 publications
9
31
2
Order By: Relevance
“…Indeed, the Bozic, Tyler, et al (2013) study was conducted on just this assumption, where forms like bravely and happiness were expected to behave, neurocognitively, in the same way as regular inflectional forms. The absence of selective LH activation, for both Polish and English transparent forms, suggests either that these forms are not in fact combinatorially processed or that such processes can also be supported by bihemispheric, potentially more domain-general systems, consistent with recent claims for aspects of syntactic processing (Bozic, Fonteneau, Su, Marslen-Wilson, 2015).…”
Section: Bihemispheric Framework For Spoken Language Comprehensionsupporting
confidence: 78%
“…Indeed, the Bozic, Tyler, et al (2013) study was conducted on just this assumption, where forms like bravely and happiness were expected to behave, neurocognitively, in the same way as regular inflectional forms. The absence of selective LH activation, for both Polish and English transparent forms, suggests either that these forms are not in fact combinatorially processed or that such processes can also be supported by bihemispheric, potentially more domain-general systems, consistent with recent claims for aspects of syntactic processing (Bozic, Fonteneau, Su, Marslen-Wilson, 2015).…”
Section: Bihemispheric Framework For Spoken Language Comprehensionsupporting
confidence: 78%
“…This interpretation of our brain imaging results are aligned with the predictions of the dualsystems framework described in the introduction (Marslen-Wilson et al, 2014;Tyler & Marslen-Wilson, 2008), where it's expected that inflectional morphology will rely on brain regions including the left IFG. Other studies, including ones that have been designed to probe this framework, have also observed more extensive activation of left BA44 with increasing combinatorial load where inflectional morphology was involved (Bozic et al, 2007(Bozic et al, , 2015Carota et al, 2016;Klimovich-Gray et al, 2017;Schell et al, 2017). The specificity of our findings to the anterior-ventral Cluster 3 of BA44 is consistent with recent brain imaging findings on variations in combinatorial load within one language (Schell et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Inflectional morphology, which is computationally more complex, is expected to induce activation in the left hemisphere fronto-temporal regions (i.e., dorsal BA44 and pSTG), while derivational morphology is expected to engage bilateral temporal regions (i.e., STG and MTG; Klimovich-Gray, Bozic, & Marslen-Wilson, 2017). These predictions are borne out in studies having examined specific languages having different degrees of morpho-syntactic complexity, such as English, Arabic, Polish, Russian, and Italian (Boudelaa, Pulvermuller, Hauk, Shtyrov, & Marslen-Wilson, 2010;Bozic, Fonteneau, Su, & Marslen-Wilson, 2015;Bozic, Marslen-Wilson, Stamatakis, Davis, & Tyler, 2007;Carota, Bozic, & Marslen-Wilson, 2016;Klimovich-Gray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, key studies that illustrate asymmetries between these regions -namely, that the posterior temporal lobe is associated with hierarchical processing while Broca's area is associated with linear processing. A series of fMRI studies by Tyler and colleagues has found that pMTG activates for simple phrasal stimuli, but that the response in pIFG is preferentially driven by inflected word forms, which rely on linear morpho-syntactic computations (Tyler et al, 2004;Bozic et al, 2015). Additionally, a recent fMRI study by Brennan et al (2016) localized language-responsive regions of interest (ROIs) in individual subjects and then tested parsing models with an increasing degree of hierarchical information, from linear sequences, to simple hierarchical phrase structure, and finally to more complex transformed syntactic structures.…”
Section: Syntax 27mentioning
confidence: 99%